Waw sargonicum on parataxis in sargonic royal inscriptions - Kogan, Leonid 1973- (2014)
According to a widespread belief, the prepositive connective conjunction *wa-, a highly prominent Common Semitic syntactic feature, is generally lost in Akkadian, where it is replaced by the postpositive -ma. The article investigates the paratactic structures of the earliest syntactically informative documents written in Akkadian, the Sargonic royal inscriptions, in an attempt to show that the role of the connective u in this corpus is radically different from what we find in its later analogues. This fact may have some implications for the diachronic background of the connective element /u/ in Sumerian. As for the history of the Akkadian parataxis as a whole, interesting structural parallels to it are found on the opposite extreme of the Semitic-speaking world, in the modern Semitic languages of Ethiopia.